Objective measurement of photopic illuminance rate in daily life of progressive myopic children - Tanrıverdi, Cafer; Nurözler Tabakçı, Burcu; Kılıç, Aylin; Mrochen, Michael C. (Assoc Research Vision Ophthalmology Inc, 2019)
[Abstract Not Available]
Conference: Annual Meeting of the Association-for-Research-in-Vision-and-Ophthalmology (ARVO) Location: Vancouver, CANADA Date: APR 28-MAY 02, 2019
Keywords: Progressive Myopic Children; Photopic; Objective Measurement